REVIEW MENGENAI PENINGKATAN KUAT TEKAN BETON YANG TERKEKANG SECARA SEMPURNA DENGAN EKSTERNAL NATURAL FIBER REINFORCED POLYMER (NFRP) - Nazira Suha Al Bakri; Taufiq Saidi; Muttaqin Muttaqin (Prodi Magister Teknik Sipil Unsyiah, 2022)
Structural strengthening is needed in buildings that experience a decrease in serviceability, inappropriate quality of existing concrete, and unexpected natural events such as earthquakes. One method that has been widely used for structural strengthening is external restraint using synthetic Fiber Reinforced Polymer (FRP). External restraints on concrete can significantly increase the strength and ductility of concrete. The use of Fiber Reinforced Polymer (FRP) material requires a relatively expensive cost and a production process that is not environmentally friendly, so alternative Natural Fiber Reinforced Polymer (NFRP) materials are needed that are environmentally friendly, renewable, and relatively cheaper, such as jute, hemp, cotton, abaca and basalt. This research review aims to determine the behavior of confined concrete with external Natural Fiber Reinforced Polymer (NFRP) and the increase in compressive strength due to confinement. The test is carried out by providing an axial load on the concrete test object which is restrained by NFRP. NFRP restrained specimens are made by wrapping the entire concrete in a circle using natural fibers and adhesives. The results obtained from this research review are the compressive strength of confined concrete using several types of natural fibers such as jute, hemp, cotton, abaca and basalt, it is found that the type of fiber and the number of layers of NFRP affect its compressive strength. NFRP showed a significant restraining effect on increasing the compressive strength and increasing the ductility of the concrete. The increase in strength and ductility will increase with an increase in the number of layers of Natural Fiber Reinforced Polymer (NFRP).